The Impact of Mental Illness Stigma on Psychiatric Emergencies - da Silva, Antônio Geraldo; Baldaçara, Leonardo; Cavalcante, Daniel A.; Fasanella, Nicoli Abrão; Palha, Antônio Pacheco (Frontiers in Psychiatry, 2020)
Psychiatric emergencies are changes in behavior that place the patient or others at risk and require immediate therapeutic intervention (within minutes or hours) to prevent harm. Representing extreme severity in mental illness, they are associated with feelings of fear, anger, prejudice and even exclusion. Professional and environmental aspects of the healthcare workplace can help perpetuate stereotypes and interfere with care quality. Stigma can lead to very negative consequences in patients with mental disorders. Certain measures can reduce stigma and provide a more dignified way for patients to recover from the crisis. This article aims to discuss the causes of stigma, ways of dealing with it, and achievements that have been made in psychiatric emergency care settings.